Peran Interaksi Anak-Anak Dalam Pengembangan Kemampuan Bahasa Di Kelompok Bermain Ra Ar Rohmah Kalibatur Tahun Ajaran 2024/2025 - Fitria Susanti; Prisca Sampe; Izak Jakobis Makulua; Rusnawati Ellis; Neleke Huliselan (Jurnal Inovasi Pendidikan Dan Pembelajaran, 2025)
This study aims to determine the role of interaction between children in playgroups at RA Ar Rohmah Kalibatur in the 2024/2025 Academic Year on the development of language skills. The language skills of early childhood are very important as a basis for their cognitive, social, and emotional development. Social interactions that occur in playgroups play a major role in stimulating speaking, listening, and communicating skills effectively. The method used in this study is descriptive qualitative with a case study approach. The results of the study indicate that interactions between children in playgroups at RA Ar Rohmah Kalibatur in the 2024/2025 Academic Year can improve their language skills, especially in the aspects of speaking, listening, and communicating with peers.